A Robust and High Self‐Healing Efficiency Poly(Urea‐Urethane) Based on Disulfide Bonds with Cost‐Effective Strategy. Issue 23 (30th October 2019) - Wang, Yulong; Li, Yaqiong; Bai, Jingjing; Li, Zhenzhong; Hu, Guosheng
Abstract: The development of self‐healing poly(urea‐urethane)s with remarkable mechanical properties as well as self‐healing capability is an important challenge through a low‐cost approach. In this study, cystine dimethyl ester (CDE) is synthesized cost‐effectively using cystine from bio‐based sources as raw material, and a novel self‐healing poly(urea‐urethane) is successfully prepared using synthesized CDE as a disulfide‐containing chain extender through a two‐step approach. The as‐prepared disulfide‐containing poly(urea‐urethane) (SPU) presents an excellent self‐healing capability with self‐healing efficiency of 95.3% at a moderate healing temperature (≈60 °C). Meanwhile, the SPU exhibits robust mechanical properties possessing a maximum tensile strength of 25.80 MPa and a high elongation at break of over 460% simultaneously. The compromise between self‐healing capability and mechanical performance can be responsible for the exchange of dynamic disulfide bonds and the existence of quadruple hydrogen bonding. This strategy provides an available idea to develop robust self‐healing polymer materials cost‐effectively. Abstract : A self‐healing poly(urea‐urethane) is prepared based on disulfide bonds with a cost‐effective strategy. The poly(urea‐urethane) presents an excellent self‐healing capability with self‐healing efficiency of 95.3% and high tensile strength up to 25.80 MPa. The balance between self‐healing capability and mechanical performance can be responsible for the exchanges of dynamic disulfide bonds and the existence of quadruple hydrogen bonding.